Virtual immersion in nature and psychological well-being: A systematic literature review. (April 2022) - Frost, Sharon; Kannis-Dymand, Lee; Schaffer, Vikki; Millear, Prudence; Allen, Andrew; Stallman, Helen; Mason, Jonathan; Wood, Andrew; Atkinson-Nolte, Jalasayi
Abstract: Immersion in nature provides various psychological benefits to well-being. Recent research examines whether these benefits can be replicated in virtual reality (VR). This study aimed to systematically review the literature on the psychological effects on well-being of virtual immersion in nature. Databases searched included Scopus, EBSCO, Web of Science, Psychnet, and Pubmed with inclusion of peer reviewed articles published in English, between 2015 and 2020 (inclusive to July 2020), in which the research design includes VR-based immersion in nature. A total of 21 quantitative studies were identified. Within these articles, most employed quantitative research methodologies within an experimental design. In regard to psychological well-being, some evidence suggests that virtual immersion in nature significantly decreases negative affect. Conversely, other research found no change or an increase in negative affect. Generally, no significant differences were noted for positive affect. Physiological indicators of stress responses to virtual immersion in nature varied. Overall, research exploring the use of virtual reality immersion in nature is limited and the replication of the potential benefits gained from real immersion in nature is poorly understood. Future research is required to advance understanding and knowledge of the outcomes of virtual immersion in nature on human well-being. Highlights: A PRISMA, systematic literature review on the rapidly evolving field of virtual immersion in nature and well-being. One-third of studies demonstrated that exposure to nature in virtual reality decreases negative affect. Positive outcomes were found for anxiety and trauma symptoms following virtual immersion in nature.